2013
DOI: 10.1002/aic.14112
|View full text |Cite
|
Sign up to set email alerts
|

Optimization‐based framework for computer‐aided molecular design

Abstract: A new framework to automate, augment, and accelerate steps in computer-aided molecular design is presented. The problem is tackled in three stages: (1) composition design, (2) structure determination, and (3) extended design. Composition identification and structure determination are decoupled to achieve computational efficiency. Using approximate group-contribution methods in the first stage, molecular compositions that fit design targets are identified. In the second stage, isomer structures of solution comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 76 publications
(93 reference statements)
0
81
0
Order By: Relevance
“…Detailed information for the case studies can be found in the supplementary material. Design of other molecules (Samudra and Sahinidis, 2013;Harper et al, 2001;Karunanithi et al, 2005) such as refrigerant design and various types of solvents can be obtained from the authors.…”
Section: Page 8 Of 13mentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed information for the case studies can be found in the supplementary material. Design of other molecules (Samudra and Sahinidis, 2013;Harper et al, 2001;Karunanithi et al, 2005) such as refrigerant design and various types of solvents can be obtained from the authors.…”
Section: Page 8 Of 13mentioning
confidence: 99%
“…This relaxation is justified by the fact that the average errors in first-order property estimation of the GC + model rarely exceed 10% (Samudra & Sahinidis, 2013). But it is not always easy for the users to find the appropriate relaxations.…”
mentioning
confidence: 99%
See 3 more Smart Citations